Antifungal peptides: a potential new class of antifungals for treating vulvovaginal candidiasis caused by fluconazole‐resistant Candida albicans. (19th January 2017) - Ng, Siew Mei Samantha; Yap, Yi Yong Alvin; Cheong, Jin Wei Darryl; Ng, Fui Mee; Lau, Qiu Ying; Barkham, Timothy; Teo, Jeanette Woon Pei; Hill, Jeffrey; Chia, Cheng San Brian
Abstract : Vulvovaginal candidiasis/candidosis is a common fungal infection afflicting approximately 75% of women globally caused primarily by the yeast Candida albicans . Fluconazole is widely regarded as the antifungal drug of choice since its introduction in 1990 due to its high oral bioavailability, convenient dosing regimen and favourable safety profile. However, its widespread use has led to the emergence of fluconazole‐resistant C. albicans, posing a universal clinical concern. Coupled to the dearth of new antifungal drugs entering the market, it is imperative to introduce new drug classes to counter this threat. Antimicrobial peptides (AMPs) are potential candidates due to their membrane‐disrupting mechanism of action. By specifically targeting fungal membranes and being rapidly fungicidal, they can reduce the chances of resistance development and treatment duration. Towards this goal, we conducted a head‐to‐head comparison of 61 short linear AMPs from the literature to identify the peptide with the most potent activity against fluconazole‐resistant C. albicans . The 11‐residue peptide, P11‐6, was identified and assayed against a panel of clinical C. albicans isolates followed by fungicidal/static determination and a time‐kill assay to gauge its potential for further drug development. Copyright © 2017 European Peptide Society and John Wiley & Sons, Ltd.